2007
DOI: 10.1002/uog.4070
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of transvaginal sonography and rectal endoscopic sonography in the diagnosis of deep infiltrating endometriosis

Abstract: Objectives To compare the accuracy of transvaginal sonography (TVS) and rectal endoscopic sonography (RES) for the diagnosis of deep infiltrating endometriosis (DIE), with respect to surgical and histological findings. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
3
10

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(209 citation statements)
references
References 34 publications
14
182
3
10
Order By: Relevance
“…These results are similar to those of Guerriero et al (7), who indicated a specificity of 92% and a sensitivity of 67%, but lower than those of Abrao et al (26) and Bazot et al (5,9,(27)(28)(29). On the contrary our results are superior in terms of sensitivity compared with the data reported by Grasso et al (30) (33.3% sensitivity).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Isupporting
confidence: 90%
“…These results are similar to those of Guerriero et al (7), who indicated a specificity of 92% and a sensitivity of 67%, but lower than those of Abrao et al (26) and Bazot et al (5,9,(27)(28)(29). On the contrary our results are superior in terms of sensitivity compared with the data reported by Grasso et al (30) (33.3% sensitivity).…”
Section: Mri and Tg-tvus Had A Similar Diagnostic Accuracy And Good Isupporting
confidence: 90%
“…Many studies have validated the non-surgical diagnosis of endometriomas and deep endometriosis through TV-US [14][15][16][17]. The ultrasound pattern showed similar modification in all patients: DIE plaques and nodules appeared less fibrotic and more homogeneous, with illdefined contours.…”
Section: Commentmentioning
confidence: 92%
“…Other investigators have shown that introital 3–dimensional sonography was highly effective in detecting endometriosis of the recto‐vaginal septum 15 . Bazot, et al compared the accuracy of TVS and rectal endoscopic sonography (RES) for the diagnosis of DIE and concluded that TVS is apparently more accurate than is RES for predicting DIE in specific locations, and should thus be the first‐line imaging technique in this setting 16 . Its low cost, availability and patient acceptability are also significant added advantages 23 …”
Section: Evolution Of Transvaginal Scan For Diagnosis Of Extra‐ovariamentioning
confidence: 99%